2018
DOI: 10.1021/acscatal.8b00936
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Support Effect in Selective Propane Dehydrogenation Catalyzed by Ga(i-Bu)3 Grafted onto γ-Alumina and Silica

Abstract: The reactions of Ga(i-Bu) 3 (i-Bu = CH 2 CH-(CH 3 ) 2 ) with the dehydrated and partially dehydroxylated surfaces of alumina (Al 2 O 3−500 ) and silica (SiO 2−700 ) were studied by IR, high field solid-state NMR and EXAFS spectroscopies, as well as elemental analysis. Grafting onto Al 2 O 3−500 occurs selectively by protonolysis at individual surface hydroxyl groups, resulting in the formation of mononuclear [(AlO)Ga(i-Bu) 2 L] (L = surface oxygen) sites as the major surface organometallic entities. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 65 publications
3
74
0
Order By: Relevance
“…It was found that grafting on alumina occurs mostly as in mononuclear gallium sites while grafting on silica results in dinuclear species. 113 SOMC and EXAFS spectroscopy also shine when crystalline supports with well-defined surface chemistry are used to isolate single atoms. Gates et al have notably investigated two types of supports: nonporous nanoparticles with preferentially exposed facets (e.g., MgO, TiO 2 ) and crystalline microporous solids (zeolite and metal organic framework).…”
Section: X-ray Spectroscopymentioning
confidence: 99%
“…It was found that grafting on alumina occurs mostly as in mononuclear gallium sites while grafting on silica results in dinuclear species. 113 SOMC and EXAFS spectroscopy also shine when crystalline supports with well-defined surface chemistry are used to isolate single atoms. Gates et al have notably investigated two types of supports: nonporous nanoparticles with preferentially exposed facets (e.g., MgO, TiO 2 ) and crystalline microporous solids (zeolite and metal organic framework).…”
Section: X-ray Spectroscopymentioning
confidence: 99%
“…parallels what is found for Cr (vide supra). 58,80 Note however that Al 2 O 3 also displays a considerable PDH activity and selectivity (ca. 4% conversion, E40% total activity after 20 hours onstream).…”
Section: Supported Ga III and Related Systemsmentioning
confidence: 99%
“…This phenomenon is similar to that of the GaO x catalytic system, where the activity is not a consequence of Ga nuclearities, but of the Ga-O-support interaction. 34 To further evaluate the intrinsic activity in C-H activation, propane temperature-programmed surface reaction (C 3 H 8 -TPSR) experiments were carried out over 1VZr, ZrO 2 and 1VAl. The temperature where the C 3 H 8 signal begins to drop is determined as the C-H activation temperature.…”
Section: Catalytic Performancementioning
confidence: 99%